2017
DOI: 10.1590/2317-1545v39n2171033
|View full text |Cite
|
Sign up to set email alerts
|

Physiological maturity and drying speed in the quality of zucchini ( Cucurbita pepo L.) seeds

Abstract: -Harvesting and drying are essential procedures to obtain high quality seeds as well as for their conservation during storage. The goal of this research was to identify the physiological maturity stage and to verify the effect of drying speeds on the quality of zucchini seeds. A completely randomized design in a 3x2x2 factor scheme was used, involving three fruit maturation stages (49, 56 and 63 days after anthesis -DAA), two drying speeds (slow and quick) and two storage periods (0 and 6 months). Seed quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
(37 reference statements)
0
5
0
1
Order By: Relevance
“…The drying rate in the first period N will depend on the operating parameters of the drying equipment and can be represented in general by the equation [8]: According to the calculations, the unknown coefficients of the drying process are found, then the drying rate in the first period of vibration-convective drying of pumpkin seeds can be determined by the equation: 5 1.74 0.33 0.366 1, 016 10 .…”
Section: Results Of Determining the Kinetics Of The Process Of Pumpkimentioning
confidence: 99%
See 1 more Smart Citation
“…The drying rate in the first period N will depend on the operating parameters of the drying equipment and can be represented in general by the equation [8]: According to the calculations, the unknown coefficients of the drying process are found, then the drying rate in the first period of vibration-convective drying of pumpkin seeds can be determined by the equation: 5 1.74 0.33 0.366 1, 016 10 .…”
Section: Results Of Determining the Kinetics Of The Process Of Pumpkimentioning
confidence: 99%
“…UDC 633.1: 631.536.24 DOI: 10.15587/1729-4061.2020.195203 influence of drying speed on the physiological maturity of melon seed was determined in [5]. These works do not give a clear understanding of the method and equipment of the process.…”
Section: проведенI експериментальнI дослIдження процесу сушIння високmentioning
confidence: 99%
“…Seeds of Cucumis anguria cv. Liso Gibão showed the maximum dry mass accumulation at 47 DAA (Silva et al, 2019), while the highest dry mass of Cucurbita pepo was observed in seeds from fruits harvested at 49 DAA in the cultivar Caserta (Silva et al, 2017) and 50 DAA in the cultivar F1 Novita (Sanches et al, 2017). Trichosanthes cucumerina presented a small reduction in seed dry mass (1.89 g.seed −1 ) at 60 DAA, possibly due to seed respiration (Silva et al, 2019).…”
Section: Seed Maturationmentioning
confidence: 99%
“…Cucurbita pepo cv. Caserta showed maximum values of mass, germination, and vigor at 49 DAA (Silva et al, 2017). The harvest of the cultivar F1 Novita of the same species carried out at 50 DAA was the most suitable for presenting the best results on seed quality (Sanches et al, 2017).…”
Section: Seed Maturationmentioning
confidence: 99%
“…Isso se deve tanto à umidade relativa do ar e à temperatura adequadas, quanto ao reduzido teor de água das sementes (CARVALHO; NAKAGAWA, 2012). Igualmente, Silva et al (2017) Apesar de não terem causado interferência negativa sobre os resultados dos testes de emergência da plântula e de germinação das sementes de Physalis peruviana, a simples detecção merece atenção, considerando que algumas espécies dos gêneros fúngicos identificados são causadoras de danos para diversas plantas. Por exemplo, durante o armazenamento, Aspergillus spp.…”
Section: Datunclassified